Prevalence and risk factors of perinatal asphyxia in newborns in Colombia: a systematic review and meta-analysis - Agudelo-Pérez, Sergio; Mejía Echeverría, Valeria; Medellín Ortiz, Laura Valentina; García Cárdenas, Tania Dayana; Pérez Flórez, Juan Miguel; Maldonado, María José (Frontiers in Pediatrics, 2025)
BackgroundPerinatal asphyxia (PA) is a critical neonatal condition and a leading cause of morbidity and mortality, particularly in low- and middle-income countries. Despite its clinical relevance, data on the prevalence and risk factors for PA in Colombia remain limited. This study aimed to estimate the cumulative prevalence of PA and identify associated risk factors in the Colombian neonatal population.MethodsA systematic review and meta-analysis were conducted in accordance with the PRISMA guidelines. A comprehensive search of PubMed, Scopus, LILACS, and Web of Science databases was performed between July and August 2024. No restrictions were applied regarding the publication year. Data were extracted, synthesized, and analyzed using random-effects models. Heterogeneity was assessed using I2 and τ2 statistics, and potential publication bias was evaluated using Funnel Plot analysis and Egger's test.ResultsNine studies with 16,778 patients were included. The cumulative prevalence of PA was estimated to be 5.92% (95% CI: 0.00, 25.03%) with significant heterogeneity (I2 = 99.2%). Key risk factors associated with PA included meconium-stained amniotic fluid (pooled OR 7.5; 95% CI 1.4–39.6), prolonged second stage of labor (pooled OR 15.1; 95% CI 1.4–157.6), and intrapartum fetal distress (pooled OR 11.6; 95% CI 1.2–114.4).ConclusionThe findings revealed a notable burden of PA in Colombia and highlighted critical inconsistencies in the diagnostic criteria and reporting practices across studies. These results underscore the urgent need to standardize definitions, strengthen perinatal surveillance systems, and improve obstetric and neonatal care. By identifying major evidence gaps and the most consistent risk factors, this review provides a foundation for future multicenter research and for the development of targeted evidence-based interventions to reduce preventable neonatal morbidity and mortality in Colombia.